Etiology, EEG, and MRI Findings in Nonconvulsive Seizures with Impaired Consciousness - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
Nonconvulsive seizures (NCS) in children admitted to the Pediatric Intensive Care Unit (PICU) from Jan 2000 to Dec 2003 were analyzed in a study at The Hospital for Sick Children, Toronto, Ont, Canada.